1930
DOI: 10.1002/hlca.19300130540
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis des Kohlenstoffringes XV. Über die Herstellung und einige physikalische Daten verschiedener Kohlenstoffringe bis zum 32‐Ring

Abstract: A. Herstellung neuer Ringcrrbindir nyen.In verschiedenen vorhergehenden Abhandlungen wurtlc die Gewinnung neuer Kohlenstoffringe bis einschliesslitah zum SO-Ring beschrieheii. Durch diese Untersuchungen war die vollsttindige Reihe aller Kohlenstoffringe bis einschliesslich zum 22-gliedrigen und d a m nocli der 29-und der 30-gliedrige bekannt geworden. Dicse Arheiten wurden nun in zwei Richtungen weiter fortgesetzt. Zur teilweisen Ausfullung der Lucke zwischen dem 22-und dem 29-Ring wxrdeii die noch unbekannten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1932
1932
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The effect of homology within a ring itself is not so simple. The difference in the structure of small and of large rings has been pointed out previously by Ruzicka and coworkers (6,7,8). They have shown that the larger rings consist of two parallel chains of carbon atoms similar to the aliphatic chains, while in the smaller rings the arrangement is more nearly that of regular polygons; in the intermediate rings (of about eight or ten to seventeen carbon atoms) the compression of hydrogen atoms within the center of the ring gives a maximum in the density at = 14.…”
Section: Homologous Seriessupporting
confidence: 52%
“…The effect of homology within a ring itself is not so simple. The difference in the structure of small and of large rings has been pointed out previously by Ruzicka and coworkers (6,7,8). They have shown that the larger rings consist of two parallel chains of carbon atoms similar to the aliphatic chains, while in the smaller rings the arrangement is more nearly that of regular polygons; in the intermediate rings (of about eight or ten to seventeen carbon atoms) the compression of hydrogen atoms within the center of the ring gives a maximum in the density at = 14.…”
Section: Homologous Seriessupporting
confidence: 52%
“…First prepared in the 1920s and 1930s by Ruzicka et al . in connection with their work on perfumery constituents, most members of the series are beautifully crystalline, moderately high melting solids that are readily prepared (although often in low yield) by well-documented procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In order to quantify the amounts of 3 , 6 , 7 , and 8 by UV it was first necessary to determine the chromatographic retention characteristics and relative UV response factors (ε ratios) for 6−8 vs 3 . Diketone 3 was prepared by published procedures …”
Section: Resultsmentioning
confidence: 99%
“…All glassware was oven-dried. Diketone 3 was prepared as previously described, except THF was used as solvent, rather than benzene …”
Section: Methodsmentioning
confidence: 99%